Balloon angioplasty for uncontrollable hypertension caused by coral reef aorta: A case report. Issue 6 (December 2021) - Nishio, Ryo; Matsumoto, Daisuke; Noiri, Jun-ichi; Takeshige, Ryo; Konishi, Hiroki; Matsuzoe, Hiroki; Ozawa, Makito; Inoue, Kyozo; Takaishi, Hiroshi
Abstract: Coral reef aorta is a stenosis of the aorta due to severe calcification. We report the case of a 74-year-old woman with coral reef aorta whose hemodynamics were physiologically similar to those found in patients with renovascular hypertension. The patient had resistant hypertension, refractory edema, and renal dysfunction. Bilateral renal artery stenosis and infrarenal aortic stenosis were suspected after a Doppler ultrasound examination. Evaluation by intravascular ultrasound and pressure wire revealed that the high blood flow caused by infrarenal aortic stenosis derived from the high-flow velocity in a renal artery without stenosis. Angioplasty with balloon improved the stenosis, and the patient was relieved from a spiral of uncontrollable hypertension, edema, and renal dysfunction. This rare case was a patient with coral reef aorta who was diagnosed with uncontrollable hypertension and angioplasty was performed effectively and minimally invasively. <Learning objective: Coral reef aorta should be considered as a diagnosis for patients suspected to have renovascular hypertension. Furthermore, angioplasty with balloon is an effective treatment approach.>